Chemical modification of the adeno-associated virus capsid to improve gene delivery. Issue 4 (17th December 2019) - Mével, Mathieu; Bouzelha, Mohammed; Leray, Aurélien; Pacouret, Simon; Guilbaud, Mickael; Penaud-Budloo, Magalie; Alvarez-Dorta, Dimitri; Dubreil, Laurence; Gouin, Sébastien G.; Combal, Jean Philippe; Hommel, Mirja; Gonzalez-Aseguinolaza, Gloria; et al.
Abstract : Bioconjugated AAV vectors, achieved by coupling of ligands on amino groups of the capsid, are of great interest for gene delivery. Chemical modifications can be used to enhance cell tropism and to decrease interactions with neutralizing antibodies. Abstract : Gene delivery vectors based on adeno-associated virus (AAV) are highly promising due to several desirable features of this parent virus, including a lack of pathogenicity, efficient infection of dividing and non-dividing cells and sustained maintenance of the viral genome. However, the conclusion from clinical data using these vectors is that there is a need to develop new AAVs with a higher transduction efficiency and specificity for relevant target tissues. To overcome these limitations, we chemically modified the surface of the capsid of AAV vectors. These modifications were achieved by chemical coupling of a ligand by the formation of a thiourea functionality between the amino group of the capsid proteins and the reactive isothiocyanate motif incorporated into the ligand. This strategy does not require genetic engineering of the capsid sequence. The proof of concept was first evidenced using a fluorophore (FITC). Next, we coupled the N -acetylgalactosamine ligand onto the surface of the AAV capsid for asialoglycoprotein receptor-mediated hepatocyte-targeted delivery. Chemically-modified capsids also showed reduced interactions with neutralizing antibodies. Taken together, our findings reveal the possibility of creating a specific engineered platform for targeting AAVs via chemical coupling.